2017
DOI: 10.1021/acs.orglett.7b01633
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Huperzine Q

Abstract: The total synthesis of huperzine Q was accomplished. The synthesis features the construction of the cis-hydrindane skeleton via a Diels-Alder reaction and a ring contraction reaction of an epoxyketone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…This showed that the stereocongested compound 79 was accessible via a semi-pinacol rearrangement of epoxide 77, which was synthesized from the chiral pool chemical (R)-piperitone in three steps. 2 The synthesis of huperzine Q (8) featured selective epoxide cleavage via a 1,2-carbon shift in the preparation of product 82 89 (Scheme 4(E)). Exposure of epoxide 80 to TMSOTf enabled the selective opening of the epoxide, resulting in 1,2-carbon migration giving ketoaldehyde 82 in 91% yield.…”
Section: Semi-pinacol Rearrangements In Natural Product Synthesismentioning
confidence: 99%
“…This showed that the stereocongested compound 79 was accessible via a semi-pinacol rearrangement of epoxide 77, which was synthesized from the chiral pool chemical (R)-piperitone in three steps. 2 The synthesis of huperzine Q (8) featured selective epoxide cleavage via a 1,2-carbon shift in the preparation of product 82 89 (Scheme 4(E)). Exposure of epoxide 80 to TMSOTf enabled the selective opening of the epoxide, resulting in 1,2-carbon migration giving ketoaldehyde 82 in 91% yield.…”
Section: Semi-pinacol Rearrangements In Natural Product Synthesismentioning
confidence: 99%
“…We used a Diels-Alder reaction and a ringcontraction reaction to construct the cis-hydrindane skeleton of huperzine Q. 13,14 The Diels-Alder reaction of the cyclohexenone 10 with the siloxydiene 11 was mediated by zinc chloride to afford 12 as a mixture of isomers, which were oxidized with 2,3-dichloro-5,6-dicyano-p-benzoquinone (DDQ) to produce the ,-unsaturated ketone 13. Formation of a nitrogen-containing nine-membered ring by a three-step sequence, followed by nucleophilic epoxidation, afforded epoxy ketone 14.…”
Section: Synthesis Through Changes In the Ring Sizementioning
confidence: 99%
“…Finally, in 2017, Fukuyama group also reported their synthesis of (±)‐ 13 . As shown in Scheme c, a Diels‐Alder reaction installed the cis ‐decaline ring ( 137 ).…”
Section: Fawcettimine Alkaloids With Level 2 Oxidation State At C16mentioning
confidence: 99%